Kollektiv mobilisering: Samfunnsarbeid i teori og praksis (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2022)
Collective mobilization arises in the context of social movements and people’s desire for change. In this book, collective mobilization is discussed in light of a variety of perspectives, theories and methodological entryways. Grassroots mobilization is an important principle in community work along with citizen collaboration, influence, and co-creation in the development of local environments and communities. This anthology explores current issues related to welfare policies and practices, as well as global challenges associated with environmental and societal problems. The authors show how community work as a subject, theory, method, and field of research can contribute to greater understanding and development of sustainable solutions. The chapters include examples from a minority organization’s work to counteract negative social control, peer-support consultants’ contributions in treatment programs, young persons’ entry into and resolution of conflicts on social media, union organization of women in India, and neighborhood development planning in urban areas. With Freire’s consciousness-raising teachings on teamwork and Putnam’s and Bourdieu’s ideas about social capital as an underpinning, the authors examine how collective mobilization happens and how it is exercised. As such, the book is a contribution to disciplines and educational programs within the social sciences and social professions. Collective Mobilization is relevant for students, researchers and practitioners within various disciplines and professional areas where collective approaches to society’s challenges are of interest. The book is the result of a collaboration that originated in the community work research group at Western Norway University of Applied Sciences. The editors are Gudmund Ågotnes and Anne Karin Larsen, associate professor and associate professor emerita, respectively, at Western Norway University of Applied Sciences. Kollektiv mobilisering har sitt utgangspunkt i sosiale bevegelser og menneskers ønsker om forandring. I denne boken diskuteres kollektiv mobilisering i lys av ulike perspektiver, teorier og metodiske innganger. Et viktig prinsipp i samfunnsarbeid er grasrotmobilisering og innbyggernes samarbeid, innflytelse og samskaping i utvikling av eget nærmiljø og lokalsamfunn. Antologien tar opp tidsaktuelle problemstillinger relatert til velferdssamfunnet, samt globale utfordringer knyttet til miljømessige, sosiale- og samfunnsmessige problem. Forfatterne viser hvordan samfunnsarbeid som fag, teori, metode og forskningsfelt kan bidra til økt forståelse og utvikling av bærekraftige løsninger. Kapitlene belyser eksempler hentet fra en minoritetsorganisasjons arbeid for å motvirke negativ sosial kontroll, erfaringskonsulenters medvirkning i behandlingstilbud, ungdoms inngang til og løsning av rollekonflikter på sosiale medier, fagorganisering av kvinner i India og områdesatsing i byområder. Med utgangspunkt i Freires bevisstgjørende samhandlingspedagogikk og Putnams og Bourdieus forståelse av sosial kapital undersøker forfatterne hvordan kollektiv mobilisering oppstår og utøves. Slik bidrar boken til samfunnsvitenskapens og sosialprofesjonenes fag og utdanninger. Boken retter seg mot studenter, forskere og praktikere innen ulike yrkes- og fagområder som er opptatt av kollektive tilnærminger til samfunnsmessige utfordringer. Antologien er et resultat av forfattersamarbeid som springer ut av forskningsområdet samfunnsarbeid ved Høgskulen på Vestlandet. Redaktører for boken er førsteamanuensis Gudmund Ågotnes og førstelektor emerita Anne Karin Larsen, begge ved Høgskulen på Vestlandet.